PENGARUH EARNING SURPRISE POSITIF TERHADAP REAKSI PASAR - Sang Ayu Putu Piastini Gunaasih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
This study investigates empirically the effect of positive earning surprise to the market response by using event study method. The investigation is opted by referring to the previous investigation results, yet by applying market adjusted model with cross section model. Cross section model is chosen since it has a long period of observation. Hence, the result is expected to be better. Moreover, the simple regression and T-testing method are employed to validate the results. The sampling data are collected from all of the companies that are registered in Indonesia Stock Exchange (BEI). The sampling data type is secondary data type. The purposive sampling method is employed for collecting the sampling data. The result reveals that positive earning surprise is responded positively by the market. Since it can perform the good news for the market when the announcement of profitability is announced. Subsequently, the result of this investigation is expected giving a contribution to the investor for making a decision of investment in the future.Keywords: Earning surprise, Market reaction, Event study